Traumatize anterior teeth, dento-facial anomalies among deaf person in the middle region of Iraq (Mustansiria Dental Journal, 2024)
This study was designed to determine the type and prevalence of trumatic dentalinjuries, aenterio—posterior molar relation among (519) deaf persons and (532) schoolstudents at 5-16 years of age in the middle region of Iraq. The study showed that theprevalence of traumatic dental injuries were 6.94% for deaf persons and 5.83% forschools students. Males showed a higher percentage of traumatized teeth than females ininstitutions and school students. Enamel dentine fracture without pulp exposure was themost predominant type among deaf persons while simple enamel fracture was the mostpredominant among schools students. The majority of deaf persons and schools studentsdemonstrated normal type of occlusion 57.42%, 55.64% respectively. Deaf personshowed significantly with percentage of 4.62% mesial full cusp deviation from normal.antero·postrior molar relation compared to school students 2.07%